PENGARUH BRAND IMAGE DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN SAUS SASA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS SINGAPERBANGSA KARAWANG - Iis Komala Sari; Endang Taufiqurahman (Jurnal Mirai Management, 2021)
This study aims to determine the effect of brand image and advertisements on the decision to purchase Sasa chili sauce in the students of the Faculty of Economics, University of Singaperbangsa, Karawang. This type of research is descriptive verification with quantitative methods. The sampling technique used purposive sampling. The number of samples in this study amounted to 100 respondents. The data analysis technique used is Path Analysis.The results of hypothesis testing are known to Sig. F≤α (0.000≤ 0.1) shows that there is a simultaneous significant effect of Brand Image and Advertising variables on Purchasing Decisions. Besides that, it can also be known sig. t≤α (0.000≤ 0.1) indicates that there is a partially significant effect of Brand Image and Advertising variables on Employee Performance. The R square value is 0.738 or 73.8%. This means that the Brand Image and Advertising variables contribute to the variable Purchasing Decision by 73.8%, while the remaining 26.2% of the Purchasing Decision variable will be influenced by other variables which are not discussed in this study. Keywords: Brand Image_1, Adversiting_2, Purchase Decision_3